Can costs of screening for hypertension and diabetes in dental care and follow-up in primary health care be predicted?. (November 2013) - Engström, Sevek; Borgquist, Lars; Berne, Christian; Gahnberg, Lars; Svärdsudd, Kurt
Abstract Aim. The purpose was to assess the direct costs of screening for high blood pressure and blood glucose in dental care and of follow-up in primary health care and, based on these data, arrive at a prediction function. Study population. All subjects coming for routine check-ups at three dental health clinics were invited to have blood pressure or blood glucose measurements; 1, 623 agreed to participate. Subjects screening positive were referred to their primary health care centres for follow-up. Methods. Information on individual screening time was registered during the screening process, and information on accountable time, costs for the screening staff, overhead costs, and analysis costs for the screening was obtained from the participating dental clinics. The corresponding items in primary care, i.e. consultation time, number of follow-up appointments, accountable time, costs for the follow-up staff, overhead costs, and analysis costs during follow-up were obtained from the primary health care centres. Results. The total screening costs per screened subject ranged from €7.4 to €9.2 depending on subgroups, corresponding to 16.7–42.7 staff minutes. The corresponding follow-up costs were €57–€91. The total resource used for screening and follow-up per diagnosis was 563–3, 137 staff minutes. There was a strong relationship between resource use and numbers needed to screen (NNS) to find one diagnosis (P < 0.0001, degree of explanation 99%). Conclusions. Screening and follow-up costs were moderate and appear to be lower for combined screening of blood pressure and blood glucose than for separate screening. There was a strong relationship between resource use and NNS.